2015
DOI: 10.1126/science.aaa0494
|View full text |Cite
|
Sign up to set email alerts
|

Coping with earthquakes induced by fluid injection

Abstract: Hazard may be reduced by managing injection activities

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
113
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 198 publications
(114 citation statements)
references
References 18 publications
1
113
0
Order By: Relevance
“…The potential for anthropogenic activities to trigger earthquakes has been widely acknowledged by the scientific community [31][32][33][34]. In particular, the generation mechanisms and magnitudes of anthropogenic earthquakes depend on several factors, such as the volume of the injected or extracted fluids, the extent of the perturbation [35], the geometry and orientation of the fault planes, the hydraulic connection between the injection and extraction zones and the fault planes [14], the magnitude of the tectonic stress field, and the distance between anthropogenic activities and earthquake source.…”
Section: Discussionmentioning
confidence: 99%
“…The potential for anthropogenic activities to trigger earthquakes has been widely acknowledged by the scientific community [31][32][33][34]. In particular, the generation mechanisms and magnitudes of anthropogenic earthquakes depend on several factors, such as the volume of the injected or extracted fluids, the extent of the perturbation [35], the geometry and orientation of the fault planes, the hydraulic connection between the injection and extraction zones and the fault planes [14], the magnitude of the tectonic stress field, and the distance between anthropogenic activities and earthquake source.…”
Section: Discussionmentioning
confidence: 99%
“…It is well established that flow through natural or hydraulically induced fractures is of particular importance to the production of oil, natural gas, water, and geothermal energy, and understanding crack flow is vital in connection with waste fluid disposal by deep injection, CO 2 , and natural gas storage underground, and in radioactive wastes containment (Davies et al, 2013;Green et al, 1988;McGarr, 2014;Wilson et al, 2015). Its importance has long been recognized in connection with the hazard of induced earthquakes (Fang et al, 2017;Guglielmi et al, 2015;Healy et al, 1968;McGarr et al, 2015;Rubinstein & Mahani, 2015). Townend and Zoback (2000) recognized the importance of cracks in permitting sufficient fluid interconnectivity in otherwise low matrix permeability rocks such that a hydrostatic fluid pressure distribution can be maintained at least to midcrustal depths, in order to satisfy the constraints of in situ stress determinations in deep boreholes.…”
Section: Introductionmentioning
confidence: 99%
“…However, the AER is in charge of monitoring these events through the Regional Alberta Observatory for Earthquakes Studies Network. Research into induced seismicity from oil field operations has found that fracking has created predominantly micro-earthquakes (too small to be felt) but there has been evidence of larger events where damage has occurred [37].…”
Section: Induced Seismicitymentioning
confidence: 99%